Library seat and book availability checking using mobile application - Choong, Jun Mun (2022)

(untitled)
Nowadays, the libraries are usually located in higher education institutions such as colleges and universities. Mostly, the students come to the libraries to do their assignments and research papers. When the UTAR students comes to the library, they will be facing some problems, such as difficult to find an available or preferred seat, hard to find exact location of the books or overwhelmed with vast amount of the books. For this purpose, a user-friendly library seat and book availability checking mobile application has been developed in this project, with the aim to help UTAR students reserving a library seat, and to locate exact location of the books. Agile development methodology is implemented to provide a development plan for this project and Android Studio is used to develop the mobile application. Furthermore, this project will replicate the real UTAR library’s seat layout. In the mobile application, there will be four floors of library shown and a seat viewing feature is implemented where the students can visualize the available seats in each floor before coming to the library. The students can zoom in or zoom out the visualized seat layout to have a better view. Students can check the real-time availability of their preferred seat and make seat reservation with the desired date and time. When the student has successfully booked the seat, the student must scan the QR code that had provided on the seat to check in the booked seat when come to the library. The purpose is to make sure that the students do not take the wrong seat. In alternatively way, the student is allowed to scan the QR code to get and check in the seat directly, provided that the selected seat is available for reservation. A search engine is provided in the proposed application so that students can use the search engine to check the availability of the book. Then, the detail information of the book such as book name and call number will be displayed. In addition, this mobile application is able to point the exact location of the books in the layout, so that students can easily pick up the book in library and it can save the user’s time from browsing the books one by one on the shelves.